Degradation on wood by insects and the effects on furniture production - Abood, Faizah (Forestry Department Peninsular Malaysia, 2008)
In the tropics, biodegradation of wood progresses rapidly due to the biologically favourable temperatures and humidity conditions all year round. The population growth rate of insects is high and they reproduce throughout the year. To understand the degradation caused by insects on wood and how it can affect furniture production, the nature of the particular insect attack and the characteristic forms of damage must be understood. In this paper, the characteristic habits of major insect pests, particularly ambrosia beetles, powderpost beetles and termites are described. The diagnostic signs of infestation and how the different forms of damage affect furniture production are discussed. Precautionary as well as remedial measures are also described.